ANALISIS DAMPAK KEBIJAKAN MONETER TERHADAP VARIABEL MAKROEKONOMI DI INDONESIA (PENERAPAN VECTOR ERROR CORRECTION MODEL) - Julaihah, SE., M.Si,, Umi (IQTISHODUNA, 2008)
The objectives of this study are to analyze the effect of monetary policy on Indonesian economy and to know policy variable such as monetary aggregate that have contribution in explain the variability of macroeconomic variables. The data sample used in this study are quarterly time series data from 1983.1 - 2003.2. Those data are base money, one month commercial bank deposit interest rate, consumer price index, gross domestic product, and exchange rate (rupiah/dollar). A method of analysis in this study is Vector Error Correction Model (VECM). The advantages of VECM are because it has: (i) impulse response function that can trace the response of one endogen variable because shock/innovation of others variables in the model; (ii) variance decomposition that can show the contribution of one variable endogen in explained the variability of others endogen variables. The result of impulse response function shows that economic growth did not response the shock of base money. Although base money has significant effect on inflation but this model leaves a price puzzle and liquidity puzzle. The result of variance decomposition shows that base money contributes only 5% on inflation but it did not give any contribution on economic growth fluctuation. The interesting result is policy variables (base money) have best contribution in explain the fluctuation on exchange rate. Then, it asserts that shock of policy variable is responded by exchange rate faster than other macroeconomic variables.